The role of CircRNA/miRNA/mRNA axis in breast cancer drug resistance - Ghazimoradi, Mohammad H.; Babashah, Sadegh (Frontiers in Oncology, 2022)
Multi-drug resistance is one of the major obstacles in the treatment of cancers. This undesirable feature increases the mortality rate of cancers, including breast cancer. CircRNA/miRNA/mRNA is one of the important axis with major roles in the promotion and resistance of breast cancer. This heterogeneous pathway includes mRNA of oncogenes and tumor suppressors, which are controlled by miRNAs and CircRNAs. Unfortunately, this network could be easily deregulated, resulting in drug resistance and tumor development. Therefore, understanding these dysregulations may thus help to identify effective therapeutic targets. On this basis, we try to review the latest findings in the field, which could help us to better comprehend this significant axis in breast cancer.